Growth and Volatility Nexus in Sub-Saharan Africa - (:unkn) unknown (WILEY, 2018)
Using cross-sectional and panel data estimation techniques with various methods of volatility measures, we have found a significant negative impact of growth volatility on growth for 35 sub-Saharan African countries from 1980 to 2013. When we consider the possible endogeneity of growth volatility, we obtained a more strong negative relationship. Decade by decade regression indicates a decline in the volatility effect over time for standard deviation based method. Nevertheless, volatility coefficient of one decade does not significantly vary from the other decade when we test for the equality of the coefficients. We further classified SSA countries into resource rich' and resource non-rich' so as to observe if volatility varies by resource within the region. Although the latter groups seem to have a stronger negative relationship, it is the resource rich' countries which have a stronger negative relationship when endogeneity of growth volatility is taken into account.
Keywords: EXCHANGE-RATE VOLATILITY; COUNTRIES; CYCLES; IMPACT; TRADE